Influence of in ovo Administration of Varying Levels of Glucose on the Hatchability Traits and Humoral Immune Response of Arbor Acres Broiler Chickens. - Akingbade, A.O.; Sogunle, O.M.; Jinadu, K.B.; Aromoye, R.A.; Orimogunje, R.; Saka, A.A.; Adewumi, M.O.; Osinubi, A.A. (Nigerian Journal of Animal Science, 2026)
In ovo feeding is a nutritional strategy employed during the embryonic stage to optimize growth performance and immune functions for sustainable poultry production. This study was conducted to investigate the effects of in ovo administration of varying levels of glucose on hatchability traits and humoral immune response of Arbor Acre broiler chickens. Two hundred (200) fertile eggs of Arbor Acres strain of broiler chickens were used for the experiment. Candling was done on the 14th day of incubation and viable eggs were distributed into five (5) treatment groups consisting of the control –T1 (no in ovo injection), T2 (Sham group-0.5ml of sterile water/egg); T3 (50mg glucose per egg); T4 (75mg glucose per egg); T5 (100mg glucose per egg) in a completely randomized design. The in ovo injection was carried out on 18th day of incubation before being transferred to the hatcher. The post-hatch chicks were replicated based on the number of chicks hatched from each treatment. Data collected on the hatching traits and immune response were subjected to descriptive statistics using 2013 Microsoft excel package. Result of hatchability showed that the hatchability percentages in T1-T5 were 83.33%, 80.00%, 63.33%, 63.33% and 43.33%, respectively. The weight of newly hatched chicks were 37.57g, 37.37g, 37.44g ,36.80g(T1) and 36.57g(T2) Results showed that chicks from eggs injected with 50 and 100 mg glucose had highest immune response to sheep Red blood cell (SRBC) antibody titre. The study concluded that glucose can be injected in ovo at 50-100 mg per egg to influence hatchability and humoral immune response of broiler chickens.